Understanding by Design in Teaching English as a Foreign Language at SMK N 2 Surakarta: A Case Study - Susanti, Sinta Ari; Setiawan, Deni; Puspitasari, Fibriani Dita; Faridah, Ely; Jannah, Inayatul; Latifah, Hanan; Hindriati, Hindriati (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2023)
There are some problems in the learning process that indicate a lack of connection between the components of learning objectives, learning experience, and evaluation. Understanding by Design becomes a solution to overcome the lack of connection between the components. Understanding by Design adopts backward design which begins with determining learning objectives. The next stage is determining assessments aligned with the previously determined learning objectives. The final step is designing learning activities which must be aligned with the learning objectives. Therefore, the components of learning, learning objectives, learning experience, and evaluation, in Understanding by Design are interrelated with one another. The purpose of this research is to analyze lesson plan development using Understanding by Design in teaching report text in the English lesson for 11th grade of SMK Negeri 2. This study used a qualitative approach using a case study method. Data collection was carried out through observation and documentation. The results of the study indicate that the development of the English lesson plan at SMK Negeri 2 Surakarta is in accordance with the Understanding by Design approach, which can be implemented by identifying desired outcomes, identifying evidence for assessment, and planning the learning process. The Understanding by Design approach, using backward design, assists teachers in developing lesson plans with interrelated components.